الوحدة العربية في السياسة الخارجية الليبية : دراسة تحليلية في أهدافها ونتائجها 1969-1999م - أبو شويشة، رقية عبد الهادي أحمد
This thesis examines the issue of Arab unity, which is a major objective of the Libyan foreign policy. It presents persistent issues concerning the achievement of a goal that is aspired by the majority of Arab nations. As this research contributes to reviving the idea of Arab unity, it therefore aims to identify the causes of failure to achieve this goal. Due to the large number of unitary initiatives in the Arab political arena, this study was limited to the Libyan foreign policy from 1969 to 1999. To achieve that purpose, the researcher utilized several approaches such as the descriptive approach in explaining and analyzing the most important initiatives of Arab unity, the critical approach in discussing the most important decisions and opinions presented by the political decision-makers, and the historical approach in probing the historical documents of those initiatives which are classified as total integration unitary projects and federal unitary projects. This study revealed several conclusions; the difficulty of separating political projects from the issue of Arab national security, which is threatened by the presence of the Zionist entity, and the importance of managing the crisis of the Arab- Israeli conflict and its impact on the issue of Arab unity. This thesis also revealed the difference of political ideologies and systems of governance in the Arab countries and the randomness and haste that prevailed over the unitary initiatives as well as the lack of prior planning and the weak culture of political institutions making such initiatives associated with leaders’ willingness only. Also, this study exposed the lack of accuracy in the agreements’ manuscript between Arab countries as it unveiled the issue of neglecting the development of thoughtful economic plans and joint development projects in the Arab World, which can ensure economic integration among those countries and form a fundamental pillar to achieve Arab unity.